2009
DOI: 10.1143/apex.2.093002
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxial Growth of NdFeAsO Thin Films by Molecular Beam Epitaxy

Abstract: Epitaxial films of NdFeAsO were grown on GaAs substrates by molecular beam epitaxy (MBE). All elements including oxygen were supplied from solid sources using Knudsen cells. The x-ray diffraction pattern of the film prepared with the optimum growth condition showed no indication of impurity phases. Only (00l) peaks were observed, indicating that NdFeAsO was grown with the c-axis perpendicular to the substrate. The window of optimum growth condition was very narrow, but the NdFeAsO phase was grown with a very g… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
50
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 21 publications
6
50
0
Order By: Relevance
“…One year later, Kawaguchi et al reported the successful fabrication of superconducting single crystalline films of F-doped Nd1111 by MBE process and found that the growth time, t g , has a crucial importance for the superconducting properties of resultant films [36]. When t g ≤ 3 h, the single crystalline films with almost no impurity phases were obtained and did not show a superconductivity, which were similar to their previous report [35]. However, when t g ≥ 4 h, the Nd1111 phase was still major one, and some impurity phases (NdOF, Fe 2 O 3 , and FeAs) appeared.…”
Section: -Systemsupporting
confidence: 75%
See 1 more Smart Citation
“…One year later, Kawaguchi et al reported the successful fabrication of superconducting single crystalline films of F-doped Nd1111 by MBE process and found that the growth time, t g , has a crucial importance for the superconducting properties of resultant films [36]. When t g ≤ 3 h, the single crystalline films with almost no impurity phases were obtained and did not show a superconductivity, which were similar to their previous report [35]. However, when t g ≥ 4 h, the Nd1111 phase was still major one, and some impurity phases (NdOF, Fe 2 O 3 , and FeAs) appeared.…”
Section: -Systemsupporting
confidence: 75%
“…The technical breakthrough is the successful fabrication of NdFeAsO (Nd1111) epitaxial thin film by molecular beam epitaxy (MBE) [35]. Although the growth window is very narrow, the single crystalline film of NdFeAsO can be reproducibly fabricated on GaAs substrate.…”
Section: -Systemmentioning
confidence: 99%
“…%, suggesting that it is difficult to incorporate a sufficient fluorine concentration to induce superconductivity in 1111 films. A similar difficulty in fluorine incorporation was also reported in the case of molecular beam epitaxy (MBE) by Kawaguchi et al 65) of Ikuta's group. They successfully obtained epitaxial films of NdFeAsO (Nd1111) on GaAs(001) substrates by choosing suitable sources and optimizing their fluxes.…”
Section: Thin Filmssupporting
confidence: 68%
“…They successfully obtained single-phase epitaxial Nd1111 films when t g 3 h, but the films did not exhibit superconductivity, similar to in their previous study. 65) On the other hand, when t g ! 3 h, the Nd1111 phase was still the major one, but some impurities (Fe 2 O 3 , FeAs, and NdOF) appeared.…”
Section: Thin Filmsmentioning
confidence: 99%
“…Toward such purposes, it is necessary to establish the technique to grow high-quality epitaxial thin films. There are some efforts already reported to prepare thin films of Fe-based superconductors, including PLD growth of Sr(Fe,Co) 2 As 2 [8], Ba(Fe,Co) 2 As 2 [9], FeS 1Àx Te x [10], and MBE growth of NdFeAs(O,F) [11]. In this article, we report our attempt at MBE growth of FeSe and (Sr,K)Fe 2 As 2 (called as (Sr,K)-122) below).…”
Section: Introductionmentioning
confidence: 99%